Teaching recent history in countries that have experienced human rights violations: case studies from Chile - Toledo, María Isabel; Magendzo, Abraham; Gazmuri, Renato (Faculty of Education, University of the Free State, 2011)
Incorporating recent history into the educational curricula of countries that have experienced human rights violations combines the complexities of teaching history, teaching recent history, and human rights education. Recent history makes a historical analysis of social reality and a historiographical analysis of the immediate. It is located between history and present, between past and present, between witness and historian, between memory and history. This situation creates problems in teaching. This article investigates the teaching-learning process of the subunit ‘Military regime and transition to democracy’ in secondary schools in Santiago, Chile, by means of both a quantitative methodological strategy to identify six unique cases, and a qualitative strategy that is reported in this article. A variety of practices highlighted four models: constructivism, development of meta-cognition, historical discourse, and moral discourse. These models are described. Their diversity is due to the existence of different theoretical frameworks. This unit has gaps in content and historiographical knowledge, and there is no coordination with human rights education. The diversity of models is cause for concern because not all of them encourage students to understand the present as a result of a historical process and how to operate within it.
Keywords: Classroom; School ethnography; Recent history; Curriculum